UNSOLICITED PPP IMPLEMENTATION IN INDONESIA: A CASE STUDY OF THE DHOHO AIRPORT PROJECT - Nugroho, Muhammad Sapto; Sari, Feby Kartika; Wismar, Luwandiko; Saputra, Olgavian Ade (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Infrastructure development is a critical driver of economic growth in Indonesia. However, limited funding from the State Budget (APBN) has prompted the Indonesian government to adopt the Public-Private Partnership (PPP) scheme. The Kediri Dhoho Airport project, designated as one of the National Strategic Projects (PSN), is the first unsolicited PPP airport project in Indonesia, initiated by PT Gudang Garam Tbk through its subsidiary, PT Surya Dhoho Investama (PT SDHI), using the Design-Build-Finance-Operate-Maintain-Transfer (DBFOMT) scheme. This single-case study analyzes the project’s success factors and identifies strong financial commitment, effective risk management, and rigorous monitoring and evaluation as key contributors to the successful implementation of the unsolicited PPP model. The findings show that the project overcame significant challenges—such as land acquisition, technical risks, and financial constraints—without any government fiscal contributions. The success of the Dhoho Project is expected to serve as a strategic model for future PPP initiatives, demonstrating that this scheme can be an effective solution for public infrastructure development in Indonesia.